Fixity and Fluidity: Embodiment of Multicultural Ethos in Damien O’Donnell’s Movie East is East (1999) - Panta, Shiva Raj; Regmi, Laxmi (Academia Research Journal, 2024)
This article is an examination of multicultural ethos in the movie East is East. Multiculturalism, in this, article stands for the policy of embracing of differing viewpoints and perspectives when two or more cultures come into contact. Through qualitative methodological mode and multiculturalism as a theoretical framework, this study utilizes the research methods such as within case analysis, comparative analysis and archival studies Within case analysis lends the ground for the intense consideration of the instances selected; comparative analysis is a mode of reasoning to segregate the attributes; archival studies offer a situation in which earlier critiques and judgments are considered for an intended conclusion. The analytical framework constitutes twofold conceptual strings: familial lynchpin’s fluidity and against bigotry. These two strings yield the analytical advancement as they contain the dialogues of the characters. Such advancement substantiates the usefulness of the multicultural attitude: the respect for all cultures, if not in the absolute sense. The implications and significance of this study can be summed up as the addition of a perspective, through the artistic means such as cinematographic representation. The added perspective in the domain of cultural studies is that multiculturalism can neither be taken to its celebratory mode nor the denigrating mode. Striking the middle math, multiculturalism is a useful notion that can help embrace the panoply of customs, values and norms. East is East, the movie as the corpus of the study renders the evidences to prove that fluidity, not fixity, in the border situations is a better option.